Expansion of the Discretion Concept Reviewed from Legal Anti-Positivism - Annisa Salsabila (Badan Strategi Kebijakan Hukum, 2022)
The terms of discretion have been determined finitely in Article 24 of Law Number 30 of 2014 concerning Government Administration. However, the requirement